Evaluation of Legal Policy Implementation in Addressing Environmental Crisis: A Case Study on Plastic Waste Management - Teguh, Adean; Syam, Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The environmental crisis caused by the escalating issue of plastic waste has garnered significant attention globally, including in Indonesia. Jambi, a region profoundly impacted, grapples with the challenge of managing plastic waste, which accounts for 50 percent of the annual waste production from 2022 to 2023. This study aims to evaluate the implementation of legal policies in addressing this environmental crisis, focusing on plastic waste management in Jambi. Additionally, it examines efforts to prevent further environmental deterioration through legal enforcement. Utilizing a qualitative approach with a case study methodology, data were gathered through interviews with various stakeholders, including governmental bodies, non-governmental organizations, and industrial sectors. Document reviews and literature surveys were also conducted to gain insights into the current state of plastic waste management in Jambi. Findings indicate that despite the existence of legal frameworks aimed at mitigating plastic waste issues, implementation remains limited, failing to significantly reduce plastic waste accumulation in Jambi. Critical factors such as inadequate inter-agency coordination, resource scarcity, and insufficient public awareness hinder effective environmental crisis management efforts. In conclusion, this research underscores the pressing need for more robust implementation of legal policies to combat the environmental crisis, particularly in plastic waste management in Jambi. Additionally, proactive measures through stringent legal enforcement are imperative to prevent further environmental degradation and safeguard the ecological integrity of Jambi's landscape.